Cumani Migrazioni, strutture di potere e società nell'Eurasia dei nomadi (secoli X-XIII) - Pubblici, Lorenzo (Europe in between. Histories, cultures and languages from Central Europe to the Eurasian Steppes, 2021)
This book is a synthesis of the great migrations of the 6th-13th centuries, focused on the median space between the two extremes of the Eurasian continent: Western Europe and Eastern Asia. In the light of the sources, it aims to reassess the complexity of the relationships between the nomads of the steppes and the sedentarized societies that came into contact with them. The choice to focus on the Qïpčaq-Cumans is due to their history, unique because they never constituted an organized and centralized center of collective power (stateless nomads); and paradigmatic, because it encompasses all the constitutive elements of steppe nomadism: social heterogeneity, mobility, military preparation, attraction for trade and willingness to negotiate. The migrations of the nomads of the steppes and their arrival close to the great organized communities of the Islamic and Christian world, from Asia to Europe, contributed to triggering a process of integration between Asia and the Mediterranean basin, a process that the Mongol invasion and conquest completed, giving birth to a new shared global space.